2007
DOI: 10.1002/pen.20744
|View full text |Cite
|
Sign up to set email alerts
|

An applicable electrospinning process for fabricating a mechanically improved nanofiber mat

Abstract: Engineered polymer scaffolds play an important role in tissue engineering. An ideal scaffold should have good mechanical properties and provide a biologically functional implant site. Considering their large surface area and high porosity, nanofibers have good potential as biomimetic scaffolds. However, the main shortcomings of scaffolds consisting of nanofibers are their mechanical inability to sustain a stress environment for neotissues and shape‐ability to form a variety of shapes and sizes. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…Puls [78] one of the purposes of which was to provide an updated version for the model for DHC as originally proposed by Dutton and Puls [16][17][18][19] by using the sign convention for tensile stress used in later versions of the model. This paper demonstrated the physical incorrectness of a model for DHC propagation proposed recently by Kim and co-workers [21,22,[71][72][73][74][75][76][77]. It also provides a rebuttal to their model in which it is suggested that hydrogen movement down a gradient of chemical potential is irrelevant and spontaneous and preferential precipitation of hydride at the crack tip upon load application is the first step for each successive stage of DHC.…”
Section: Note Added In Proofmentioning
confidence: 79%
See 1 more Smart Citation
“…Puls [78] one of the purposes of which was to provide an updated version for the model for DHC as originally proposed by Dutton and Puls [16][17][18][19] by using the sign convention for tensile stress used in later versions of the model. This paper demonstrated the physical incorrectness of a model for DHC propagation proposed recently by Kim and co-workers [21,22,[71][72][73][74][75][76][77]. It also provides a rebuttal to their model in which it is suggested that hydrogen movement down a gradient of chemical potential is irrelevant and spontaneous and preferential precipitation of hydride at the crack tip upon load application is the first step for each successive stage of DHC.…”
Section: Note Added In Proofmentioning
confidence: 79%
“…In a series of papers Kim [21,22,[70][71][72][73][74][75][76][77] has criticized this diffusion first model on the following grounds:…”
Section: Discussionmentioning
confidence: 99%
“…They determined that the fabricated electrospun fibers had orthotropic properties (tensile modulus of moving direction ¼ 19.8 MPa and perpendicular to moving direction ¼ 13.5 MPa), which resulted from the orientation of the nanofibers. [16] However, the mechanical ability of the scaffold to maintain the structure and function immediately after implantation and during remodeling is still low. Consequently, although the scaffold 3D structure is essential for cell ingrowth and vascularization, electrospun nanofibers are not suitable for fabricating 3D scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Many research scientists have been successful in determining the crystallinity of produced nanofi bers by employing alternative methods such as X-ray diff raction and diff erential scanning calorimetry (DSC). Another geometric parameter, porosity and pore size, can be measured by mercury porosimetry (Kim et al 2007, Nair et al 2005.…”
Section: Geometric Characterizationmentioning
confidence: 99%